§ 2.

                  14. f(x)
g(x) :
                ) «»;                  
                ) .
14.01.
f(x)=25+3x4 4x3+ x2 6x + 2,
g(x) = x3 + 32 + 4 + 2;
14.02.
f(x) = 5x4+2x3x2+ 4x 5,
g(x) = x3 + 22 2 + 1;
14.03.
f(x) = 26 + 2x4 x3 + 3x2 x + 3,
g(x) = x4 + 3 + 32 + 3 + 2;
14.04.
f(x) = 25 + x4 x3 + 5x2 + 4x 1,
g(x) = x3 + 2 + 1;
14.05.
f(x) = 44 2x3 + x2 + x + 24,
g(x) = 23 2 + ;
14.06.
f(x) = 65+13x43x37x2+6x+2,
g(x) = 3x2 + 5 4;
14.07.
f(x) = 64 5x3 + 3x2 x + 7,
g(x) = 22 + 5 3;
14.08.
f(x) = 5 x4 + 2x3 x2 + 4x 5,
g(x) = x3 + 22 2 + 1;
 
14.09.
f(x) = 24 + 2x3 3x2 2x + 4,
g(x) = 3 2 + 2 1;
14.10.
f(x) = 25 + x4 + 2x3 x2 + 3x + 4,
g(x) = x3 + 22 1;
14.11.
f(x) = 46 2x5 + 4x4 + x3 2 + 4,
g(x) = 24 + 3 2 + 2;
14.12.
f(x) =155+10x42x340x 3,
g(x) = 3x3 2 + 4;
14.13.
f(x)=106+13x5+23x4+74x3252-x+27
g(x) = 22 + 8;
14.14.
f(x) =5+2x43x32x2 + 4x 5,
g(x) = x3 + 22 2x + 1;
14.15.
f(x) =x5+2x4+3x3+32 + 2 6,
g(x) = x3 + 22 + 1;
14.16.
f(x) = 2x4 + 2x3 3x2 2x + 4,
g(x) = x3 2 + 2x 1;
14.17.
f(x) = 4x5 + 3x4 + 2x3 + 3,
g(x) = x3 + 22 3 + 1;
14.18.
f(x) = 2x4 + 3x3 + x 6,
g(x) = 22 3x + 13;
14.19.
f(x) =x6+x53x4x3+42 +  2x + 4,
g(x) = x4 + 2x3 32 + 1;
14.20.
f(x) =x6+2x53x4+8x3x2+x+12,
g(x)=x43x3 52 + 3x + 2;
14.21.
f(x) = x7 + 3x6 4x5 + 11x4 7x3 + 122 59x + 3,
g(x) = x5 + 3x3 + 22 + 8 1;
14.22.
f(x) = x5 + x4 + x3 3x2 + 2x 1,
g(x) = x3 + 2 x 1;
14.23.
f(x) = 2x5 x4 + 3x3+2x+8,
g(x) = x4 + 2x3 2 + 3x 4;
14.24.
f(x) = 2x6 + 3x5 x4 + x3 22 + 6,
g(x) = x4 2x2 + 6 4;
14.25.
f(x) = 2x8 x7 + 3x6 2x5+32,
g(x) = x5 + 2x4 3 3;
14.26.
f(x) = x7 9x6 + 18x5 23x4 4x3 + 302 22x + 4,
g(x) = x5 2x4 + 33 8 + 2;
14.27.
f(x) = 2x4 3x3 + 4x2 5x + 6,
g(x) = 2 3x + 1;
14.28.
f(x) = 3x5 3x4 2x3 + 3x + 2,
g(x) = 2 1;
14.29.
f(x) = 5x5 + 4x4 + 6x32x23x+7,
g(x) = x3 22 + 3x 2;
14.30.
f(x) = 2x5 5x3 8x,
g(x) = x3 2 x;
14.31.
f(x) = 2x5 3x4 + x3+4x22x+3,
g(x) = x3 2 + 3x + 2;
14.32.
f(x) = x5 2x4 +x3+x2x1,
g(x) = x3 + 1;
14.33.
f(x) =4x52x4+4x3+x2+x3,
g(x) = 2x3 + 22 + x 2;
14.34.
f(x) = 2x5 + x4 2x3+2x2+x+1,
g(x) = 2x3 + x2 + 1;
 
14.35.
f(x) =6x5+13x43x37x2+6x + 2,
g(x) = 2x3 + 2 1;
14.36.
f(x) =2x5+3x4 x3+2x24x + 1,
g(x) = x3 + x2 + + 1.

 

\..\

                              Copyright © 2008-2009 ..   . .